2015
DOI: 10.1590/abd1806-4841.20153372
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life index in autoimmune bullous dermatosis patients

Abstract: BACKGROUNDAutoimmune bullous dermatoses are complex diseases triggered by autoantibodies action against epidermal antigens or the dermoepidermal junction. Blisters and vesicles that evolve with erosion areas characterize them. Although rare, they present high morbidity, affecting the quality of life of patients.OBJECTIVESTo assess the magnitude of autoimmune bullous dermatoses on life quality of patients treated in a public university service in countryside of Brazil.METHODSThis cross-sectional study was based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 17 publications
5
33
0
Order By: Relevance
“…Further investigation of HRQoL in this group is necessary . There is little information on HRQoL in bullous diseases: one study reported severe impairment of life quality, which is consistent with our findings …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further investigation of HRQoL in this group is necessary . There is little information on HRQoL in bullous diseases: one study reported severe impairment of life quality, which is consistent with our findings …”
Section: Discussionsupporting
confidence: 90%
“…[29][30][31] There is little information on HRQoL in bullous diseases: one study reported severe impairment of life quality, which is consistent with our findings. 32 Patients with pruritus, urticaria and prurigo had low EQ-VAS and adjusted EQ-VAS scores, similar to those with psoriasis, AD and connective tissue diseases. OR for pain/discomfort and depression/anxiety was 3-8-fold.…”
Section: Discussionmentioning
confidence: 82%
“…It may be localized to one area, or widespread on the trunk and proximal limbs. 1,3 BP is likely to have psychological and social implications for the patient since it is a chronic condition. Both clinical symptoms and the effects of treatment can have a strong impact on physical and emotional status.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of AIBD affecting the mouth is often delayed because of the uncommon nature of these diseases, the non‐specific clinical presentations, and the unfamiliarity of healthcare providers with oral mucosal diseases (Sarumathi, Saravanakumar, Datta, & Nagarathnam, ; Scully et al., ; Sirois et al., ). Importantly, delays in diagnosis and management of AIBD can adversely affect disease progression, treatment response and prognosis resulting in patient suffering, increased treatment duration and cost, and reduced productivity and quality of life (Fitzpatrick & Newcomer, ; Heelan, Mahar, Walsh, & Shear, ; Penha, Farat, Miot, & Barraviera, ; Sirois et al., ).…”
Section: Introductionmentioning
confidence: 99%